1993
DOI: 10.1073/pnas.90.16.7513
|View full text |Cite
|
Sign up to set email alerts
|

Plants transformed with a cistron of a potato virus Y protease (NIa) are resistant to virus infection.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Previous results demonstrated that the NIa proteinase of tobacco vein mottling potyvirus (TVMV) conferred protection against infection by TVMV, although not against other potyviruses (Maiti et al, 1993). Similar results were obtained with the NIa protein of PVY (Vardi et al, 1993). Our work extends these results to a third potyvirus, TEV.…”
Section: Pathogen-derived Resistance Against Multiple Viruses In Plansupporting
confidence: 79%
“…Previous results demonstrated that the NIa proteinase of tobacco vein mottling potyvirus (TVMV) conferred protection against infection by TVMV, although not against other potyviruses (Maiti et al, 1993). Similar results were obtained with the NIa protein of PVY (Vardi et al, 1993). Our work extends these results to a third potyvirus, TEV.…”
Section: Pathogen-derived Resistance Against Multiple Viruses In Plansupporting
confidence: 79%
“…Natural recessive resistances to PSbMV exist (Alconero et al, 1986 ;Provvidenti & Alconero, 1988 b) but have yet to be introgressed into commercial pea lines. The strategy of engineered resistance against potyviruses has been used successfully using viral coat protein, sense (Lindbo & Dougherty, 1992) and antisense (Hammond & Kamo, 1995), NIa protease (Maiti et al, 1993 ;Vardi et al, 1993), NIb replicase (Audy et al, 1994) and VPg sequences (Swaney et al, 1995). However, the majority of the work has been performed in Nicotiana tabacum and N. benthamiana and it remains to be determined how effective these strategies will be in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…The fi rst application of PDR phenomenon with respect to plant viruses was demonstrated by Powell-Abel et al ( 1986 ) who showed that transgenic tobacco plants expressing tobacco mosaic virus coat protein gene were resistant to attack by the tobacco mosaic virus. Examples of pathogenderived genes include the replicase protein (Rubino and Russo 1995 ), coat protein (Lindbo and Dougherty 1992 ;Nelson et al 1993 ;Ganesan et al 2009 ), proteinase (Vardi et al 1993 ), movement protein (Cooper et al 1995 ) or genes coding for host cell lethal proteins like antiviral compounds (ribosome-inhibiting proteins) (Wang et al 1998 ) or those that target the viral genome or particle directly, viz., ribozymes and ribonucleases (Sano et al 1997 ). Resistance against viruses can also be obtained by presetting the RNA silencing system in plants by introducing and expressing fragments of sense and antisense viral nucleic acid sequences into chromosomes of the plants (Prins et al 2008 ;Tyagi et al 2008 ;Duan et al 2012 ), or by expressing the virus mini-replicon (Brumin et al 2009 ), or by expression of artifi cial microRNA (Niu et al 2006 ).…”
Section: Virusesmentioning
confidence: 99%